Sports As An Instrument For Social Change In Time of Crises With A Focus On Children: The Case of Syria - Saleh, Ghada Ahmad (Πανεπιστήμιο Πελοποννήσου, 2014)
The purpose of this experimental research was to show whether sport is an instrument for social change in time of crises, with a focus on children, using a case study in Syria. The research was applied to families and their children, my target group who were forced by terrorists to leave their houses and live inside a school as a Temporary Residential Center Summayya-Al-Makhzoumieh (TRCSAM) in Damascus, provided by the Syrian government. The research was under the name of "Challenge 2013", as an individual initiative by me to introduce some help as a sport activities program to these families and their children. There were forty families inside the TRCSAM. All the families came from the countryside of the cities in Syria: Damascus, Aleppo, Homs and from other cities in Syria. All the families were living in the countryside. Now the countryside became dangerous due of terrorists invaded the countryside and forced these families to leave their houses. The program was divided into groups according to the age of the participants (group A from 3-5 years, the number of boys and girls was 20 ) (group B from 6-7years the number of boys and girls was 5) (group C from 8-13 years the number of girls was 16 and boys 30 ). See Appendix 2-List of photos , In addition to some mothers and some girls aged about 14-18 from TRCSAM. Regarding research method and collected data were through: 1- some literature reviews that related to the topic I wrote about and that I searched in the websites, some booklets and journals, scientific articles, and other materials provided me with other experiences and knowledge that I benefited from. 2- Interviews were essential in “Challenge 2013” to be more confidence of myself and my work and to give my target group (children and their mothers who were sample participants) and volunteer coaches a chance to talk about their participation in the program and to express about their feelings and experiences at time of and before of “Challenge 2013”. All interviews I made with the participants were through video camera. I was recording what I was asking them about of what was related to their participation and their feelings and they were answering directly. I made an interview with: the president of Syrian Olympic Committee, three main volunteer coaches participated in "Challenge2013" from 6 coaches, three volunteer assistant coaches (students/ girls/ from the institute of physical education), some mothers and some children. The interviews had a big role in making the experimental research successful. See Appendix 1-List of interviews. 3- Also I depended on my private observations to my target group and how did they behaved at time of and before of the program. The duration of the program started from 1/5/2013 until 1/11/2013. The variables assured that that sport and physical activity could be: 1- part of daily life for most participants who lived inside TRCSAM; 2- A big role in enhancing skills training and developing self-control, cognitive skills, motor and mental coordination in children, and cooperation and confidence among participants. Also the variables in the research introduced important data and outcomes made me more informed on how to develop and broaden the research to include other residential centers.
Keywords: Physical education for children - Curricula - Syria; Physical education - Research - Syria; Physical education and training - Case study - Syria; Φυσική αγωγή για παιδιά - Προγράμματα - Συρία; Φυσική αγωγή - Έρευνα - Συρία; Φυσική αγωγή και εκπαίδευση - Περιπτωσιακή μελέτη - Συρία; Physical education; Self-control; Cognitive skills; Motor coordination; Cooperation; Case study; Φυσική Αγωγή; Αυτοέλεγχος; Κινητικός συντονισμός; Συνεργασία; Περιπτωσιακή μελέτη